Industry 4.0: Digital Transformation of Manufacturing Industry of the Republic of Belarus - I. A. Zubritskaya (Цифровая трансформация, 2019)
The article systematizes theoretical and methodological approaches to the economy and the organization of new industrial technologies, including Industry 4.0, the trends of influence of technical and technological megatrends on the economic development of society. Based on the theoretical and methodological framework refined interpretation of the concept "digital technology" and "digital transformation of manufacturing industry" and also developed the ideal model digital industrial enterprises included in the organizational-economic mechanism of the digital transformation of the manufacturing industry of the Republic of Belarus.